Development of Halal Tourism as A Soft Power Instrument: A Comparative Study of Saudi Arabia and United Arab Emirates in The Post-Vision 2030 Era - Dwi Wahyu Khairunnisa; Mulawarman Hannase; Shobicatul Aminah (Journal Of Social Science (JoSS), 2026)
This study examines the development of halal tourism as a soft power instrument in Saudi Arabia and the United Arab Emirates in the post-Vision 2030 era. The background of this research is rooted in the rapid growth of the global Muslim-friendly travel market and the increasing use of tourism as a tool for nation branding, cultural diplomacy, and international influence. The purpose of this study is to compare how Saudi Arabia and the UAE utilize halal tourism to strengthen their global image and expand their soft power. This research employs a qualitative-comparative method using a multiple case study approach. Data were collected through document analysis of official policy reports, tourism strategies, global halal economy reports, and relevant academic literature. The findings show that Saudi Arabia builds its halal tourism strategy through sacred legitimacy as the Custodian of the Two Holy Mosques, supported by Vision 2030, pilgrimage service transformation, heritage tourism, and mega-event diplomacy. Meanwhile, the UAE develops halal tourism through cosmopolitan branding, luxury hospitality, advanced infrastructure, and Muslim-friendly services. The study concludes that halal tourism is not merely an economic sector but a strategic mechanism of soft power, with each country applying different models based on its identity, resources, and global positioning.